Making Sense of the Self: Developing an Understanding of the Role of Objects within the Reading Experience - Pecoskie, Jennifer L. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
In understanding pleasure reading in everyday life we often focus on the text as a primary tool of reading and other tools, such as books, which are instrumental objects, are overlooked. This report of qualitative research focuses on the book as a tool within reading experiences and how it furthers understandings of the self for the reader. En tentant de comprendre la lecture de loisir dans la vie quotidienne, nous considérons souvent le texte comme l’outil principal de lecture, alors que d’autres dispositifs, tels que les livres, qui sont des objets instrumentaux, sont souvent négligés. Ce rapport de recherche qualitative est axé sur le livre comme outil à l’intérieur des expériences de lecture et sur la manière avec laquelle celui-ci favorise la compréhension de la personnalité du lecteur.